2000
DOI: 10.1016/s0022-5223(00)70090-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of operations for ascending aortic dissections

Abstract: In both acute and chronic ascending aortic dissections, (1) circulatory arrest is associated with low early mortality; (2) with normal sinuses and valve, supracoronary repair of the dissected aortic root and valve resuspension is effective long term; and (3) residual distal dissected aorta does not decrease late survival and has a low risk of aneurysmal change and reoperation for at least 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
121
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(132 citation statements)
references
References 27 publications
6
121
2
3
Order By: Relevance
“…Our relatively conservative surgical approach seems to be reasonable for patients experiencing at least one of various preoperative complications, or elderly, from previous reports showing that elderly patients tended to have a thrombosed false lumen after initial surgery for AAAD. 8) Ten-year survival rates ranged from 37% to 71% in previously reported cases, 11,[15][16][17][18] 77% survival rate at 10 years in our institution seems acceptable. DeBakey et al reported that rupture of the distal aorta was the most common cause of death among patients with AAAD, accounting for 29.3% of 205 late deaths.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our relatively conservative surgical approach seems to be reasonable for patients experiencing at least one of various preoperative complications, or elderly, from previous reports showing that elderly patients tended to have a thrombosed false lumen after initial surgery for AAAD. 8) Ten-year survival rates ranged from 37% to 71% in previously reported cases, 11,[15][16][17][18] 77% survival rate at 10 years in our institution seems acceptable. DeBakey et al reported that rupture of the distal aorta was the most common cause of death among patients with AAAD, accounting for 29.3% of 205 late deaths.…”
Section: Discussionmentioning
confidence: 66%
“…11,[15][16][17][18][19] Larger numbers of patients with a longer follow-up period may be recommended for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Far fewer studies have been published on results of examination of the operatively resected portion of the ascending aorta. [11][12][13][14][15][16][17][18][19][20][21] The present report focuses on aortic medial elastic-fiber structure in 69 patients having portions of the ascending aorta operatively resected because of acute dissection involving the ascending aorta with or without involvement of other portions of the aorta.…”
mentioning
confidence: 99%
“…23 25 In the surgical management of the acute type A dissection, although valve-sparing techniques are widely used by many surgeons, the standard procedure, namely, supracoronary replacement of the dissected ascending aorta with Teflon felt or glue reconstruction of the dissected aortic root is still attractive because of its simplicity, short operation time and reduced mortality rates. [25][26][27][28] This technique has been proven by several authors inasmuch as the freedom from reoperation for aortic valve dysfunction was 91% to 82% after 10 years. 8,28 The major drawback of this technique is the need of reoperation due to sinus of Valsalva aneurysm.…”
Section: Discussionmentioning
confidence: 98%
“…The technical approach to acute type A aortic dissection that we follow in our institution is supported by many other authors. 12,[24][25][26][27][28][29][30] We recommend the use of a simple tube graft replacement in most cases except for Marfan syndrome, other known connective tissue disorders, or frank annuloaortic ectasia. The vast majority of patients with acute type A aortic dissection can be treated appropriately with a simple supracommissural tube graft.…”
Section: Discussionmentioning
confidence: 99%